VD_FINDINFO Arrêt / 2017 / 607 vom 7. September 2017 - VD Tribunal cantonal (2017)
AM, PRIME D'ASSURANCE-MALADIE, OBLIGATION DE COTISER, MAINLEVÉELP | 13 LAMal, 6 LAMal, 61 LAMal, 64a LAMal, 26 al. 1 LPGA, 61 let. a LPGA, 105a OAMal, 105b OAMal, 90 OAMal